Factors influencing gig workers’ satisfaction and commitment in the knowledge service providing platforms based on the self-determination theory: The case study in China - Yang, Liqian; Panyagometh, Aweewan (Kasetsart Journal of Social Sciences, 2023)
With the development of technology, knowledge service providing platforms are growing quickly. There were 1,021 financial investments totaling up to 131.3 billion yuan in knowledge service providing platforms in the past seven years. The gig economy has also been widely discussed in the last decade. However, the previous research studies on the gig economy mostly focused on shared transport and food delivery; thus, there is still a research gap regarding the gig economy in knowledge service providing platforms. This research is based on the self-determination theory (SDT) with the aim to study how social capital, gig workers’ intrinsic motivation, and extrinsic motivation influence their work satisfaction and commitment, with this study focus on the gig workers who work in the top six knowledge service providing platforms in China. Online questionnaires were distributed to the respondents to conduct the survey, and a total of 1049 valid respondents were received. The study compared two groups: the gig workers with full-time jobs and the gig workers without a full-time job. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to analyze the data and generate the results. It was found that both groups of gig workers, those with full-time jobs and those without have the same direction in which self-determination and social capital are positively associated with intrinsic motivation. Both intrinsic and external motivation have a positive influence on gig workers’ job satisfaction and commitment. Finally, the academic and practical contributions are discussed.